Radiocabon Dates on Bones of Extinct Birds from Hawaii - James, H. F.; T. W. Stafford Jr.; D. W. Steadman; Olson, S. L.; Martin, P. S.; Jull, A. J. T.; McCoy, P. C. (Proceedings of the National Academy of Sciences, 1987)
Bones from a stratified sedimentary deposit in the Puu Naio Cave site on Maui, Hawaiian Islands, reveal the late Holocene extinction of 19 species of birds. The age of the sediment and associated fauna was determined by direct radiocarbon dating (tandem particle accelerator-mass spectrometer; TAMS) of amino acids extracted from bones weighing as little as 450 mg. The 14C dates indicate that sediment has been accumulating in the lava tube for at least the last 7750 years, a suitable time frame for testing the hypothesis that Holocene extinction on islands began after human colonization. Despite growing evidence that a worldwide wave of extinctions coincided with human colonization of oceanic islands, little radiometric data have been available to date the extinction of most small fossil vertebrates on islands. The TAMS technique of dating purified collagen from the bones of small vertebrates could lead to vastly improved chronologies of extinction for oceanic islands where catastrophic mid- to late-Holocene extinction is expected or known to have occurred. Chronologies derived from nonarcheological sites that show continuous sedimentation, such as the Puu Naio Cave deposit, may also yield key evidence on the timing of earliest human settlement of Oceania.
Keywords: biology paleontology